Construction of Assessment Index System Model of Higher Art Teaching Quality Based on Fuzzy Clustering Algorithm - Wang, Xueyan (RISTI : Revista Ibérica de Sistemas e Tecnologias de Informação, 2023)
To improve the instructional quality, the school must first improve the instructional quality, and the instructional assessment is to judge whether the instructional quality meets certain requirements. [...]an objective, fair, scientific and effective assessment of teachers instructional quality is crucial to the survival and growth of schools. In classroom teaching, students have the most direct observation of teachers teaching behavior, and the relationship between teachers teaching and students is the closest. [...]students are most qualified to be the subject of instructional assessment. Based on the characteristics of classroom instructional quality, it is impossible to assess classroom instructional quality completely objectively and subjectively. Because many indicators used for instructional assessment are fuzzy, or classroom instructional quality assessment is a fuzzy phenomenon. In the process of instructional quality assessment, the collected data should contain all aspects of educational assessment content as much as possible to improve the quality of data [13,14]. [...]universities need to create intelligent learning environment and facilities for students.